Electronic Life Cycle Monitoring System for Various Types of Lead Acid Batteries - Žydrūnas Kavaliauskas; Igor Šajev; Giedrius Blažiūnas; Giedrius Gecevičius (Applied Sciences, 2023)
With the development of renewable sources of electricity, more and more attention is paid to electricity storage systems and their research. In order to make the research process of various types of batteries automatic, an automatic system for monitoring of the working characteristics and parameters of batteries was created. System management is based on the ATmega328 series microcontrollers. The system control program code and computer application were created using programming languages C and Delphi. The developed system is able to support the automated process of battery testing and to inform the operator about the deviations that have occurred by offering solutions. After the development of this system, a study of the charging and degradation process of four types of batteries was carried out. Four types of lead-based batteries (non-deep cycle battery, deep-cycle battery, GEL battery and AGM battery) were used for the research. Research has shown that GEL-type batteries have the highest number of life cycles, with the number of cycles reaching up to 750. This type of batteries is best suited for storing electricity obtained using renewable energy sources.